2019
DOI: 10.1590/1413-812320182411.05782018
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre os tipos de aleitamento materno e o consumo de vitamina A e ferro em crianças de 6 a 12 meses

Abstract: Resumo O objetivo deste artigo é analisar a associação entre o tipo de aleitamento no primeiro semestre de vida e o consumo de vitamina A e ferro do 6º ao 12º mês. Estudo de coorte com 226 crianças. Avaliou-se o tipo de aleitamento do 1º ao 6º mês de vida e o consumo alimentar do 6º ao 12º mês. O consumo de nutrientes entre os grupos foi comparado pelo teste Kruskal-Wallis. A análise da associação entre o consumo de nutrientes e o tipo de aleitamento se deu pela Regressão de Poisson. O consumo abaixo da recome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…An observational study that evaluated children from ve European countries observed inadequate intake of iron, iodine, folate, and vitamin D 29 . The study by Silva et al analyzed 226 children aged between six and 12 months of age and, similarly, found that 67.7% had iron consumption below the individual recommendation 20 . The maternal pro le was characterized as follows: mean age of 26 years, and most had more than nine years of schooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study that evaluated children from ve European countries observed inadequate intake of iron, iodine, folate, and vitamin D 29 . The study by Silva et al analyzed 226 children aged between six and 12 months of age and, similarly, found that 67.7% had iron consumption below the individual recommendation 20 . The maternal pro le was characterized as follows: mean age of 26 years, and most had more than nine years of schooling.…”
Section: Discussionmentioning
confidence: 99%
“…The power to test whether there is a difference between the percentages of insu cient iron intake in the BLISS and PLW groups was 94.9%. This value, applying continuity correction, was obtained considering a signi cance level of 5%, a sample size equal to 35 subjects for the BLISS group and 43 subjects for the PLW group, the prevalence of inadequate intake was considered 26% for the BLISS group and 67.7% in the PLW group 9,20 . This calculation was performed using the PSS Health® tool online version 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Verificou-se no estudo de Neu et al (2013), que o tipo de aleitamento prevalente foi o misto, uma vez que a maioria das crianças foram amamentadas no peito e na mamadeira. Silva et al (2019), avaliaram em seu estudo a influência do tipo de aleitamento materno e a relação com o consumo de vitaminas nos primeiros anos de vida e concluíram que, as crianças que estavam em aleitamento materno misto, artificial ou que não foram amamentadas até o 6º mês de vida apresentaram menor consumo de vitamina A.…”
Section: Discussionunclassified
“…Ferroenzymes and other ferroproteins participate in enzymatic systems, which are essential for cellular functions such as energy production through their role in the electron transport chain (ETC), DNA, RNA and protein synthesis, cholesterol catabolism, collagen metabolism and neurotransmitter metabolism. Iron is also important in many other metabolic functions related to growth, immunity, muscular activity, bone strength and the nervous system (Blanco‐Rojo & Vaquero, 2019; Carpenter & Mahoney, 1992; Silva et al., 2019).…”
Section: Iron In Human Nutrition and Its Bioavailabilitymentioning
confidence: 99%